Uncontrolled donation after circulatory death: European practices and recommendations for the development and optimization of an effective programme. (17th February 2016) - Domínguez‐Gil, Beatriz; Duranteau, Jacques; Mateos, Alonso; Núñez, Jose R.; Cheisson, Gaelle; Corral, Ervigio; De Jongh, Wim; Del Río, Francisco; Valero, Ricard; Coll, Elisabeth; Thuong, Marie; Akhtar, Mohammed Z.; et al.
Summary: The shortage of organs remains one of the biggest challenges in transplantation. To address this, we are increasingly turning to donation after circulatory death (DCD) donors and now in some countries to uncontrolled DCD donors. We consolidate the knowledge on uncontrolled DCD in Europe and provide recommendations and guidance for the development and optimization of effective uncontrolled DCD programmes.